2008
DOI: 10.1111/j.1574-6968.2008.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosome gene cluster analysis for gauging the diversity of the ruminal cellulolytic bacteriumRuminococcus flavefaciens

Abstract: Ruminococcus flavefaciens is a vital cellulosome-producing fibrolytic rumen bacterium. The arrangement of the cellulosomal scaffoldin gene cluster (scaC-scaA-scaB-cttA-scaE) is conserved in two R. flavefaciens strains (17 and FD-1). Sequence analysis revealed a high mosaic conservation of the intergenic regions in the two strains that contrasted sharply with the divergence of the structural sca gene sequences. Based on the conserved intergenic regions, we designed PCR primers in order to examine the sca gene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 30 publications
(39 reference statements)
6
57
0
3
Order By: Relevance
“…It thus seems that their sequence features that would account for the observed specific coupling and promiscuous behavior may be a function of simple evolutionary events. Nevertheless, there is evidence that the various subtypes may represent distinct lineages whose descendants are maintained in the rumen of subsequent generations (20). Indeed, such distinct lineages related to R. flavefaciens strains 17 and FD-1 have been identified in the rumens of contemporary animals, and the possibility would exist for similar cross-strain interactions with some strains exhibiting a propensity for sharing their components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It thus seems that their sequence features that would account for the observed specific coupling and promiscuous behavior may be a function of simple evolutionary events. Nevertheless, there is evidence that the various subtypes may represent distinct lineages whose descendants are maintained in the rumen of subsequent generations (20). Indeed, such distinct lineages related to R. flavefaciens strains 17 and FD-1 have been identified in the rumens of contemporary animals, and the possibility would exist for similar cross-strain interactions with some strains exhibiting a propensity for sharing their components.…”
Section: Discussionmentioning
confidence: 99%
“…Both strains share marked similarities in their properties. They produce elaborate cellulosomes of similar overall architecture and exhibit high sequence homology within the sca gene cluster (19,20). Surprisingly, affinity-based assays showed that CohE from R. flavefaciens strain 17 recognizes dockerins of its own strain exclusively (supplemental Fig.…”
Section: Biophysical Characterization Of the Rfcohe-xdoc Interaction-mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Nevertheless, the sequencing of the genome of cellulosome-producing bacteria revealed that their organisation varies significantly; for instance, some cellulosomes contain several interacting scaffoldins and their assembly requires several specific cohesin/dockerin docking systems. [4][5][6] At the opposite end of the scale are the simplest cellulosomes, such as those produced by some mesophilic Clostridia that are characterized by a unique scaffoldin and only one type of cohesin/dockerin docking system. 7 A typical example of "simple" cellulosome is constituted by the cellulolytic complexes secreted by C. cellulolyticum.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of this gene cluster has been documented in at least five different strains of R. flavefaciens (Jindou et al, 2008). Additionally, one peculiar and very interesting ORF containing only a signal peptide and an autonomous cohesin module (i.e.…”
Section: Introductionmentioning
confidence: 98%